New Scientific Facilities and Directions in Molecular Astrophysics - Gautam, Arjun Kumar (Himalayan Physics, 2013)
A brief overview is given of major current and future observational facilities which will enable new scientific opportunities in the study of interstellar and circumstellar molecules , ranging from the early universe to protoplanetary disks and exoplanatory atmospheres. Close interaction between astronomers and laboratory astrophysicists will be essential to read the full scientific harvest from these major investments. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 102-105 Uploaded date: 12/23/2013